Improving Graduate Employability through Internship Programs - Maria Baron-Puda (Barometr Regionalny)
A mismatch between qualifications and skills demanded and supplied is one of the main problems in the labor market. It concerns also higher education graduates. They have the theoretical background, however their abilities to apply knowledge in a work situation are insufficient. The main aim of this paper is to present the contribution of the internship program to the employability of graduates of University of Bielsko-Biala. The paper consists of three parts. The first describes changes in unemployment by educational background in the Bielsko-Biała labor market in 2010–2015. The second part includes employment prospects for graduates, with a special focus on the benefits of the internship program. The final part emphasizes the role of cooperation between the university and employers to ensure better preparation of graduates for the labor market. The paper was based on available statistical data on unemployment in the Bielsko-Biała labor market, and on the results of the surveys among employer representatives and students who participated in the internship programs within two European projects realized in University of Bielsko-Biala over 2010–2015. The research confirmed that a lack of experience reduces the chances of graduates to obtain suitable employment. Moreover, research findings proved that the internship program, developed and implemented in close cooperation with local companies, may increase employment opportunities after graduation. There is, therefore, a clear need for further cooperation between education and business in order to facilitate the transition of graduates from education to employment, as well as to satisfy labor market needs.